2017
DOI: 10.1515/cdbme-2017-0084
|View full text |Cite
|
Sign up to set email alerts
|

Stopping power accuracy and achievable spatial resolution of helium ion imaging using a prototype particle CT detector system

Abstract: A precise relative stopping power map of the patient is crucial for accurate particle therapy. Charged particle imaging determines the stopping power either tomographically -particle computed tomography (pCT) -or by combining prior knowledge from particle radiography (pRad) and x-ray CT. Generally, multiple Coulomb scattering limits the spatial resolution. Compared to protons, heavier particles scatter less due to their lower charge/mass ratio. A theoretical framework to predict the most likely trajectory of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…In this experimental study, we have demonstrated that the phase II pCT scanner prototype could be operated in PBS mode at acceptable pileup levels. Previous mentions of scanner operation in proton PBS mode did not present pileup analyses . The chosen cyclotron current of 4 nA led to a scanner trigger rate of approximately 400 kHz.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In this experimental study, we have demonstrated that the phase II pCT scanner prototype could be operated in PBS mode at acceptable pileup levels. Previous mentions of scanner operation in proton PBS mode did not present pileup analyses . The chosen cyclotron current of 4 nA led to a scanner trigger rate of approximately 400 kHz.…”
Section: Discussionmentioning
confidence: 98%
“…The pCT Phase II scanner had been so far mostly used with broad proton beams: either a passively scattered cone beam at the Loma Linda University Medical Center, covering the whole field of view of the scanner, or at the Northwestern Medicine Chicago Proton Center with a wobbled proton beam of 4–7 cm FWHM spot size . The single report of scanner operation in PBS mode makes no mention of pileup . Before performing the calibration and imaging runs, a study was made on the detector performance for a 1.37 cm FWHM PB, concentrating especially on the resulting pileup in the silicon strips of the tracker modules.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations